2017
DOI: 10.1111/cbdd.13062
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and biological evaluation of a platinum‐carbazole conjugate

Abstract: Cisplatin resistance is caused, in part, by the efficient removal of the helix-distorting cisplatin 1,2-intrastrand cross-links by nucleotide excision repair (NER) machinery.To make a platinum-DNA adduct that causes less helical distortion than the cisplatin 1,2-intrastrand adduct, we designed and synthesized a monofunctional platinumcarbazole conjugate (carbazoplatin). The 2.5 Å crystal structure of carbazoplatin-DNA adduct revealed both the monoplatination of the N7 of a guanine (G) base and the intercalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…As known, there are at least several DNA repair systems in the human body, such as nucleotide excision repair (NER), base excision repair (BER) and mismatch repair (MMR) 9 . Among them, NER is the most significant and flexible one for excising platinum‐DNA adducts 10 . The main repair steps of NER include the separation of double helix at lesion sites, the excision of the lesion‐containing single stranded DNA fragment, the synthesis of a new DNA fragment to replace the gap and the ligation of the remaining single‐stranded nick 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As known, there are at least several DNA repair systems in the human body, such as nucleotide excision repair (NER), base excision repair (BER) and mismatch repair (MMR) 9 . Among them, NER is the most significant and flexible one for excising platinum‐DNA adducts 10 . The main repair steps of NER include the separation of double helix at lesion sites, the excision of the lesion‐containing single stranded DNA fragment, the synthesis of a new DNA fragment to replace the gap and the ligation of the remaining single‐stranded nick 11 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Among them, NER is the most significant and flexible one for excising platinum-DNA adducts. 10 The main repair steps of NER include the separation of double helix at lesion sites, the excision of the lesioncontaining single stranded DNA fragment, the synthesis of a new DNA fragment to replace the gap and the ligation of the remaining single-stranded nick. 11 Therefore, the NER pathway plays a pivotal role in repairing platinum-DNA adducts and may affect the sensitivity of individuals to platinum chemotherapy potentially.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Carbazole derivatives may exert antitumor effects by inhibiting topoisomerases. 23–25 For example, ellipticine (5,11-dimethyl-6 H -pyrido[4,3- b ]carbazole) with carbazole as the main pharmacophore is a clinically approved topoisomerase inhibitor, and its derivatives exhibit inhibitory activity in several tumor types. 26…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a monofunctional platinum–carbazole conjugate with an ethylene diamine linker was more cytotoxic than CDDP. 23 The conjugate exerted different physical and biological effects depending on the platinum core, the topoisomerase inhibitor, and the linker. Recently we found that monofunctional Pt II complexes containing pyridine and –CH 2 Ph 3 P + moieties not only disrupt the function of mitochondria, 29 but also inhibit the activity of DNA topoisomerases.…”
Section: Introductionmentioning
confidence: 99%